Thioester-containing proteins regulate the Toll pathway and play a role in Drosophila defence against microbial pathogens and parasitoid wasps - Anna Dostálová; Samuel Rommelaere; Mickael Poidevin; Bruno Lemaitre (BMC Biology, 2017)
Abstract Background Members of the thioester-containing protein (TEP) family contribute to host defence in both insects and mammals. However, their role in the immune response of Drosophila is elusive. In this study, we address the role of TEPs in Drosophila immunity by generating a mutant fly line, referred to as TEPq Δ , lacking the four immune-inducible TEPs, TEP1, 2, 3 and 4. Results Survival analyses with TEPq Δ flies reveal the importance of these proteins in defence against entomopathogenic fungi, Gram-positive bacteria and parasitoid wasps. Our results confirm that TEPs are required for efficient phagocytosis of bacteria, notably for the two Gram-positive species tested, Staphylococcus aureus and Enterococcus faecalis. Furthermore, we show that TEPq Δ flies have reduced Toll pathway activation upon microbial infection, resulting in lower expression of antimicrobial peptide genes. Epistatic analyses suggest that TEPs function upstream or independently of the serine protease ModSP at an initial stage of Toll pathway activation. Conclusions Collectively, our study brings new insights into the role of TEPs in insect immunity. It reveals that TEPs participate in both humoral and cellular arms of immune response in Drosophila. In particular, it shows the importance of TEPs in defence against Gram-positive bacteria and entomopathogenic fungi, notably by promoting Toll pathway activation.